The role of cyclooxygenase inhibitors in lipopolysaccharide-induced hypophagia in chicken - Zendehdel, M.; Baghbanzadeh, A.; Yeganeh, B.; Hassanpour, S. (Czech Journal of Animal Science, 2015)
Previous studies showed that cyclooxygenase 1 (COX) enzyme has an important role in lipopolysaccharide (LPS)-induced hypophagia in mammals but the effect of COX on LPS-induced hypophagia has not been studied in avian species. The current study was designed to investigate the effects of Indomethacin, a non-selective cyclooxygenase inhibitor, Aspirin (irreversible cyclooxygenase inhibitor), Piroxicam (a selective COX-1 inhibitor), and Celecoxib (a selective COX-2 inhibitor) on LPS-induced hypophagia in 3-h food-deprived (FD3) cockerels. One hundred and sixty ROSS 308 chickens were randomly divided into 5 experiments and 4 treatment groups (8 replicates in each group of experiments). Guide cannula was surgically implanted into the lateral ventricle of chickens. In Experiment 1, birds received LPS (5, 10, and 20 ng) intracerebroventricularly (ICV). In Experiment 2, chickens were intraperitoneally (i.p.) injected with Indomethacin (5 mg/kg) prior to LPS injection (20 ng; ICV). In Experiment 3, birds were i.p. injected with Aspirin (50 mg/kg) followed by LPS injection (20 ng; ICV). In Experiment 4, chickens were given LPS (20 ng; ICV) after Piroxicam injection (10 mg/kg; i.p.). In Experiment 5, chickens were injected with Celecoxib (10 mg/kg; i.p.) prior to LPS injection (20 ng; ICV). Cumulative feed intake was determined until 8 h post-injection. According to the results, LPS significantly decreased feed intake at 4 and 8 h post injection in birds (P ≤ 0.05). Furthermore, LPS-induced hypophagia was attenuated by pre-injection with Indomethacin, Aspirin, and Celecoxib (P ≤ 0.05). However, Piroxicam had no effect on LPS-induced hypophagia (P ≥ 0.05). These results suggest that presumably COX-2 mediates LPS-induced hypophagia in broilers.
Keywords: prostaglandins; cytokines; food intake; broiler